PENERAPAN ALGORITMA GENETIK PADA PROSES PENYUSUNAN KELOMPOK BELAJAR DI SEKOLAH - Kurnia Angga; Jati Lestari (Universitas Budi Luhur, 2012)
Develop a study group at school is conducted manually and take a long times to compile the result. Moreover, the review of the group is done many times; therefore, it takes along times. Based for this reason it needs an automatic study group system. Genetic algoritm is an alternative in solving the problem, which serves as the brain to organize the study group. How to represent the problem into a chromosome is the primary key of this algorithm. Chromosome encoding process is using integer permutation. Chromosome length is determined by the number of students (male and female). The number of genes determined from the depth of static single snake formation (SSF depth). The method used is the elitism which used half of the population with the lowest fitness value and then will be eliminated. Cross over operator used is a single crossing point, by choosing the initial locus and subsequent locul will be exchanged with each other. By using the original data for each existing study program, this application will not has trouble in developing study group and of course has a far better performance compare to manual preparation of the study group.Keywords : Genetic algorithms, study group